ChemInform Abstract: Synthesis, Crystal Structure, and Magnetism of A2Co12As7 (A: Ca, Y, Ce—Yb). Issue 25 (June 2016) - Tan, Xiaoyan; Ovidiu Garlea, V.; Chai, Ping; Geondzhian, Andrey Y.; Yaroslavtsev, Alexander A.; Xin, Yan; Menushenkov, Alexey P.; Chernikov, Roman V.; Shatruk, Michael
Abstract: Intermetallic Ln2 Co12 As7 (Ln: Y, Ce—Yb) and Ca2 Co12 As7 are prepared by solid state reaction of the elements using excess Bi as a flux (evacuated silica tubes, 1223 K, 8 d).